PEMBERIAN WASIAT MELEBIHI KETENTUAN DITINJAU DARI KOMPILASI HUKUM ISLAM (KHI) (STUDI KASUS PUTUSAN NOMOR 0027/PDT.G/2017/PTA.PBR) - Mahfuza Rozaldy (Jurnal Hukum Adigama, 2022)
When a person dies, several things must be considered before the estate is distributed, includinggrants, wills, and will grants. But these three don't always have to be there when the heir passes away.The grant has entered into force while the grantor is still alive while the will grant and the grant willonly take ef ect after the grantor or grantor has passed away. But in some cases, the enactment of willsand grants of wills is sometimes not by the existing rules. As in the Religious Court Decision No.0214/Pdt.G/2017/PA.Pbr. In this case, the Will giver wrote a will containing a grant by giving all hisproperty to one of his children only, even though the Will giver had not yet died. Thus, this eventcannot be classed as a will or grant of a will. It can be concluded that the will should have beencanceled because it was not in line with the decrees that had been regulated in Islamic law and that thewill was not included in the granted class, a will or grant of a will. After all, it does not meet theelements that must be met to be categorized as a grant. After all, the letter reads a will, and neithercan it be categorized as a will nor a will grant because the will has been executed directly after theletter has been made while the will is still alive.